Evaluating the Alignment between Intended Project Durations and Standard Time Cost Models: A Comparative Analysis in Basic Hospital Construction Projects in Nepal - Dahal, Diksha; Kumar Bhattarai, Subash; Shrestha, Ronald; Khanal, Pratik; Acharya, Sagar (International Journal on Engineering Technology, 2024)
This study examines the congruence between the intended projected duration expressed in bidding documents for basic hospital construction projects and Nepal’s time cost model specific to health building projects. Through a comparative analysis approach, data from bidding documents and the time cost model equation were analyzed to identify disparities or alignments. The findings reveal moderate to strong positive correlations between the intended project completion time and the time calculated from costs, with variations in correlation strength depending on the specific variables used for cost estimation. The study highlights the need for refining cost estimation methods, enhancing training and capacity building, regular calibration of time-cost models, and further research to improve project management practices in the Nepalese construction industry.